The Influence of Managerial Ownership, Institutional Ownership, Investment Opportunity Set, and Capital Intensity on Accounting Conservatism with Political Connections as A Moderation Variable - Linda Agustina; Putri Apriliyani; Kuat Waluyo Jati (Universitas Negeri Semarang, 2022)
Purpose : This study investigates how managerial ownership, institutional ownership, investment opportunity sets, and capital intensity affect accounting conservatism moderated by political connections.Method : State-owned companies are the population in this study that went public from 2014 to 2021. A total of 17 companies per year were obtained using purposive sampling (136 units of analysis). Research data were collected using documentation techniques and analyzed using descriptive and inferential statistical analysis techniques.Findings : The findings indicate a positive relationship between institutional ownership and accounting conservatism and that high capital intensity can reduce accounting conservatism. Meanwhile, managerial ownership and investment opportunity set does not affect accounting conservatism. We also find that political connections cannot moderate the effect of managerial ownership, institutional ownership, and investment opportunity sets on accounting conservatism. However, political connections weaken the negative effect of capital intensity on accounting conservatism. Novelty : The originality of this study is in a different research model from previous research. The thing that concerns this research is based on the object used, namely BUMN companies. State-Owned Enterprises (BUMN) are the primary channel for the state to carry out its role as an economic actor. However, there are still cases of harmful accounting activities involving SOEs. So this study also emphasizes the existence of political connections, which are suspected to be one of the factors that make it difficult for companies to develop for the better.Keywords : Accounting Conservatism; Managerial Ownership; Institutional Ownership; Investment Opportunity Set; Capital Intensity; Political Connections